2005
DOI: 10.1007/s00253-005-1916-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient production of (2S)-flavanones by Escherichia coli containing an artificial biosynthetic gene cluster

Abstract: For the fermentative production of plant-specific flavanones (naringenin, pinocembrin) by Escherichia coli, a plasmid was constructed which carried an artificial biosynthetic gene cluster, including PAL encoding a phenylalanine ammonia-lyase from a yeast, ScCCL encoding a cinnamate/coumarate:CoA ligase from the actinomycete Streptomyces coelicolor A3(2), CHS encoding a chalcone synthase from a licorice plant and CHI encoding a chalcone isomerase from the Pueraria plant. The recombinant E. coli cells produced (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
148
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(149 citation statements)
references
References 25 publications
1
148
0
Order By: Relevance
“…For expression of the Ars proteins in E. coli, pETDuet-ArsA, pACYC-ArsB, pCDFArsC, pETDuet-ArsD, and pETDuet-ArsAD were constructed. In addition to these plasmids, pRSF-ACC, which carries the genes encoding the two subunits of acetyl-CoA carboxylase of Corynebacterium glutamicum, was used to increase the intracellular pool of malonyl-CoA (20,21). The vector plasmids pETDuet, pACYC, pCDF, and pRSF, which contain different replication origins and different selective markers, can be maintained together in the same E. coli cell.…”
Section: Resultsmentioning
confidence: 99%
“…For expression of the Ars proteins in E. coli, pETDuet-ArsA, pACYC-ArsB, pCDFArsC, pETDuet-ArsD, and pETDuet-ArsAD were constructed. In addition to these plasmids, pRSF-ACC, which carries the genes encoding the two subunits of acetyl-CoA carboxylase of Corynebacterium glutamicum, was used to increase the intracellular pool of malonyl-CoA (20,21). The vector plasmids pETDuet, pACYC, pCDF, and pRSF, which contain different replication origins and different selective markers, can be maintained together in the same E. coli cell.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence the host organisms provide precursors from their own primary and secondary metabolism that are converted to the expected secondary product through the expression of foreign genes. Our success in fermentative production of plant-specific polyketides by E. coli carrying an artificially assembled phenylpropanoid pathway was the first example to show that a nearly complete biosynthetic pathway in plants was established in a heterologous microorganism for production of flavanones from the amino acid precursors, phenylalanine and tyrosine [5,6]. Later, Yan et al [7] produced 5-deoxyflavanones in E. coli and Beekwilder et al [8] produced a natural raspberry ketone in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…This was accomplished by assembling PAL from the yeast Rhodotorula rubra; 4CL (ScCCL) from the actinomycete S. coelicolor A3(2); CHS from the licorice plant Glycyrrhiza echinata; and CHI from the plant Pueraria lobata on a single pET plasmid in E. coli (Fig. 4B) [5,6,30]. To maximize the expression of the four genes, various constructions of the artificial gene clusters were tested: for example, the arrangement of PAL, 4CL, CHS and CHI such that the termination codon of the preceding gene overlapped with the start codon of the following gene.…”
Section: -1 Production Of (2s)-flavanonesmentioning
confidence: 99%
“…Similarly, coexpression of two genes of C. glutamicum ACCase proved to greatly increase the overall production efficiency of flavanones, the direct precursors of the vast majority of flavonoids (Miyahisa et al, 2005). In this study (2S)-naringenin and (2S)-pinocembrin were synthesized in E. coli by employing an artificial biosynthetic cluster of genes that included phenylalanine ammonia lyase from yeast, cinnamate/coumarate:CoA ligase from the actinomycete Streptomyces coelicolor, chalcone synthase from a licorice plant, and chalcone isomerase from a Pueraria plant.…”
Section: Accase In Bacteria and Algae-based Biotech Projectsmentioning
confidence: 99%
“…In this study, coexpression of phlD and four ACCase subunits genes demonstrated the productivity of 3.8 g/L (2.1-fold change to the control strain) at large scale fed-batch fermentation conditions. This was the highest phloroglucinol production efficiency reported to date and proved that single ACCase overexpression is sufficient to greatly improve the production rate of the entire synthesis pathway.Similarly, coexpression of two genes of C. glutamicum ACCase proved to greatly increase the overall production efficiency of flavanones, the direct precursors of the vast majority of flavonoids (Miyahisa et al, 2005). In this study (2S)-naringenin and (2S)-pinocembrin were synthesized in E. coli by employing an artificial biosynthetic cluster of genes that included phenylalanine ammonia lyase from yeast, cinnamate/coumarate:CoA ligase from the actinomycete Streptomyces coelicolor, chalcone synthase from a licorice plant, and chalcone isomerase from a Pueraria plant.…”
mentioning
confidence: 99%